2019
DOI: 10.3766/jaaa.17090
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Hearing Aid Beamforming Microphone Arrays in a Noisy Laboratory Setting

Abstract: People with hearing loss experience difficulty understanding speech in noisy environments. Beamforming microphone arrays in hearing aids can improve the signal-to-noise ratio (SNR) and thus also speech recognition and subjective ratings. Unilateral beamformer arrays, also known as directional microphones, accomplish this improvement using two microphones in one hearing aid. Bilateral beamformer arrays, which combine information across four microphones in a bilateral fitting, further improve the SNR. Early bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Although in the current study the effects of DM and NR features were not examined separately, it is likely that the benefit observed in the HINT was mainly from DM technologies. The robust findings across all five listening conditions agree with previous literature regarding the efficacy of multi-channel adaptive DMs (Blamey et al 2006), bilateral beamformers (Picou & Ricketts 2018), and speech-seeking DMs (Wu et al 2013b).…”
Section: Laboratory Testssupporting
confidence: 88%
See 1 more Smart Citation
“…Although in the current study the effects of DM and NR features were not examined separately, it is likely that the benefit observed in the HINT was mainly from DM technologies. The robust findings across all five listening conditions agree with previous literature regarding the efficacy of multi-channel adaptive DMs (Blamey et al 2006), bilateral beamformers (Picou & Ricketts 2018), and speech-seeking DMs (Wu et al 2013b).…”
Section: Laboratory Testssupporting
confidence: 88%
“…Researchers also have tried to determine if premium DM and NR technologies deliver more benefit than basic technologies. Laboratory research has consistently shown that bilateral beamformers (Picou & Ricketts 2018) and speech-seeking DMs (Wu et al 2013a;Wu et al 2013b) outperform basic-level DMs. Pinna-simulation directivity can improve front-to-back localization (Keidser et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…5 In 2004, the introduction of wireless technology led to the development of innovative features such as streaming sound between hearing aids and consumer electronics products, connectivity between hearing aids and smartphones that enabled apps to give greater hearing aid control to the user, and data sharing between left-and right-worn hearing aids that enabled beamforming and other sophisticated signal processing benefits for hearing aid wearers. 6,7 In recent years, innovation has expanded beyond technology into services, business models, and product categories for new market segments.…”
Section: Innovation In Hearing Aidsmentioning
confidence: 99%
“…Generally, beamformer systems designed for hearing-aid applications try to reach a balance between SNR improvement and spatial-cue preservation (Van den Bogaert, Doclo, Wouters, & Moonen, 2008, 2009) and thus may not provide speech-in-noise benefits as large as those that are theoretically possible. Indeed, recent studies that evaluated beamforming hearing aids under relatively complex listening situations found rather modest improvements in speech intelligibility relative to standard directional microphones (e.g., Picou, Aspell, & Ricketts, 2014;Best, Mejia, Freeston, van Hoesel, & Dillon, 2015;Picou & Ricketts, 2019;V€ olker, Warzybok, & Ernst, 2015;Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%